AN ANALYSIS OF THE COLLABORATION BETWEEN PRIVATE HIGHER EDUCATION INSTITUTIONS AND KOPERTIS IN EVALUATING STUDY PROGRAM IMPLEMENTATION - Aminah (NIM 235 05 003), Siti
Abstract: The application of technology with open standards through implementation of information and communication technology (ICT) has created opportunities for organizations to develop new innovations that will enable them to run their businesses with greater flexibility on a global scale. Organizations are more dynamically able to interact with each other to solve specific problems through technology-driven solutions. The application of ICT in the educational field makes better quality in education a possibility, through the improvement of certain processes, in this case, the teaching evaluation process. The realization of good education quality is closely related to the evaluation process that is performed by a higher education institution or study program. Problems with the evaluation process usually occur because there are certain changes that need special handling. These changes include the mechanisms, processes, and implementation directives. Such changes will create great difficulties should there not be any formal business process documentation that represent the inputs, processes, outputs, and actors. Evaluation is done through evaluation activities upon all components of the teaching process. For example, evaluating the degree that learning processes have been successful. A number of aspects are scored, among others: the study program curriculum; the human resources (lecturers and supporting staff); the students; the learning process; the infrastructure; the academic environment; finances; research and publications; welfare activities for the society; governance; institutional management; information systems; cooperation with other organizations both domestic and foreign. The research investigates whether there is a possibility for the use of a business process approach to develop a collaboration in evaluation framework, which is a conceptual framework based upon concepts of evaluation, business processes, and collaboration principles. Collaboration principles as applied to the business process of evaluation have the potential to improve the evaluation implementation process. The research method used to create this collaboration in evaluation framework includes the activities of analysis, design, and evaluation. The analysis activity is done through business process modeling in order to identify the role of each process in the implementation of evaluation, and through analyses of the potential of collaboration as an effort to attain the evaluations objective (business goal). The design of this collaboration in evaluation framework is done by the representation of a model that is able to adapt in response to change, which happens to be a constraint in the implementation of evaluation. After the design of this collaboration framework, the next step is the evaluation of this framework, which is done by identifying the benefits, impact, and changes required should this framework be implemented. There is potential that the evaluation activity done by institutions of higher education and Kopertis can be improved upon through collaboration. This collaboration is designed to utilize information technology. The value obtained from this collaboration is that it can support the evaluation process by making this process easier, because it will need interaction, beginning with the study program evaluation by the institution of higher education, up to the coordination of evaluation results at a higher level by the Kopertis. The entire process needs a correct collaboration design model. Doing the collaboration using information technology support makes it possible for the interaction process to be done any time, by anybody (actors of the evaluation process), and anywhere those actors happen to be (not bound by space constraints). The two collaborating enterprises (institution of higher education and Kopertis) have different systems, including different languages, different resources, and different tools. Collaboration creates an important opportunity for the creation of model that fulfills the needs of two different systems. The design of a collaboration in evaluation framework may then be proposed, to map requirements in an interaction model between institutions of higher education and Kopertis, for the purpose of evaluation. The design of collaboration in evaluation uses two approaches, first is the collaborative business process management to establish a foundation for the framework development. This approach results in the identification of process needs and an architecture of collaboration in evaluation. Second is the collaboration system framework approach which is done by mapping more detailed collaboration needs, specifically by mapping use cases of collaboration activities, roles, function needs, collaboration service needs, and technology. This detailed design will result in the identification of requirements for a system of collaboration in evaluation. This research is now at the design stage, which is the stage where a collaboration in evaluation framework is developed. This framework represents a conceptual model using the concept of collaboration as a mutually beneficial relationship between two or more entities who cooperate towards a common goal by splitting responsibility and authority to achieve predefined objectives. Further research that can be done is the evaluation of this collaboration framework, the evaluation may be done to identify the benefits, impacts, and changes needed when this framework is applied.